The jury is still out regarding the generality of adaptive 'transgenerational' effects. (26th August 2020) - Sánchez‐Tójar, Alfredo; Lagisz, Malgorzata; Moran, Nicholas P.; Nakagawa, Shinichi; Noble, Daniel W. A.; Reinhold, Klaus
Abstract: A recent meta‐analysis concluded, ' transgenerational effects are widespread, strong and persistent' . We identify biases in the literature search, data and analyses, questioning that conclusion. Re‐analyses indicate few studies actually tested transgenerational effects – making it challenging to disentangle condition‐transfer from anticipatory parental effects, and providing little insight into the underlying mechanisms. Abstract : A recent meta‐analysis concluded, 'transgenerational effects are widespread, strong and persistent'. We identify biases in the literature search, data and analyses, questioning that conclusion. Re‐analyses indicate few studies actually tested transgenerational effects – making it challenging to disentangle condition‐transfer from anticipatory parental effects, and providing little insight into the underlying mechanisms.